Al/Ti/Al phonon-mediated KIDs for UV–vis light detection over large areas. (23rd May 2018) - Cardani, L; Casali, N; Cruciani, A; Sueur, H le; Martinez, M; Bellini, F; Calvo, M; Castellano, M G; Colantoni, I; Cosmelli, C; D'Addabbo, A; Domizio, S Di; et al.
Abstract: The development of wide-area cryogenic light detectors with baseline energy resolution lower than 20 eV RMS is essential for next generation bolometric experiments searching for rare interactions. Indeed the simultaneous readout of the light and heat signals will enable background suppression through particle identification. Because of their excellent intrinsic energy resolution, as well as their well-established reproducibility, kinetic inductance detectors (KIDs) are good candidates for the development of next generation light detectors. The CALDER project is investigating the potential of phonon-mediated KIDs. The first phase of the project allowed to reach a baseline resolution of 80 eV using a single KID made of aluminum on a 2 × 2 cm 2 silicon substrate acting as photon absorber. In this paper we present a new prototype detector implementing a trilayer aluminum–titanium–aluminum KID. Taking advantage of superconducting proximity effect the baseline resolution improves down to 26 eV.